Rozdział 8. Tryby rozstrzygania sporów inwestycyjnych ze szczególnym uwzględnieniem arbitrażu zgodnie z regulacjami Konwencji ICSID - Trnka, Krzysztof (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
Arbitration, as a method of settling investor-state disputes, generates quite a lot of controversy. It is seen as a way for private entities to circumnavigate the legal system and to secure concessions from states, often to the detriment of ordinary citizens. This paper analyzes investor-state arbitration in the European Union, utilizing statistical data published by the International Center for Settling Investment Disputes. As it turns out, the outcomes of arbitration are more often than not favourable to EU member-states. Noteworthy is also the effectiveness, with which EU-based investors use arbitration in their disputes with non-EU states.
Keywords: arbitraż; spory inwestycyjne; Międzynarodowe Centrum Rozwiązywania Sporów Inwestycyjnych; Unia Europejska; dwustronne umowy inwestycyjne